Parent’s Knowledge upon Nutritional Status of Primary School Children toward Low-Income Households in Al-Hilla City, Iraq - Abdulmahdi A. Hasan (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Nutrition has a main impact on the health promotion of school-age children, it is crucial thatthe rising energy demands that come with this age are met daily with high nutritional value foods. Schoolagechildren get a well-balanced diet, an average of 2400 calories per day required to meet growth needs, asthe child’s size grows, as well as the amount of food requiredMethod: Descriptive design study was used and get the stated objectives the period of one month (from thefirst of January, 2020 to the first of February, 2020).Results: The data analysis was indicated that the largest percentage of gender is female (97%); all of themare in the fifth class and 32% of mothers and 31% of fathers are graduated from primary school, most ofthem from urban area 86%.Conclusion: All of the children were in the 5th class—most children with normal weight. Most children havebreakfast daily. Most of the children have three meals daily. Most mothers choose easy to prepare food forher child. There is no a relationship between education of the mother and eating breakfast. However, thereare a relationship between monthly income and eating fruits .